Effects of Intracanal Irrigant MTAD Combined with Nisin at Sub-Minimum Inhibitory Concentration Levels on Enterococcus faecalis Growth and the Expression of Pathogenic Genes - Tong, Zhongchun (Public Library of Science, 2014)
Exposure to antibiotics is considered to be the major driver in the selection of antibiotic-resistant bacteria and may induce diverse biological responses in bacteria. MTAD is a common intracanal irrigant, but its bactericidal activity remains to be improved. Previous studies have indicated that the antimicrobial peptide nisin can significantly improve the bactericidal activity of MTAD against Enterococcus faecalis. However, the effects of MTAD and its modification at sub-minimum inhibitory concentration (sub-MIC) levels on Enterococcus faecalis growth and the expression of pathogenic genes still need to be explored. In this study, the results of post-antibiotic effects (PAE) and post-antibiotic sub-MIC effects (PASME) showed that MTADN (nisin in combination with MTAD) had the best post-antibiotic effect. E. faecalis after challenge with MTAD was less sensitive to alkaline solutions compared with MTAN (nisin in place of doxycycline in MTAD) and MTADN. E. faecalis induced with sub-MIC of MTAD generated resistance to the higher concentration, but induction of E. faecalis with MTAN did not cause resistance to higher concentrations. Furthermore, real-time polymerase chain reaction (RT-PCR) showed that the stress caused by sub-MIC exposure to MTAD, MTAN, or MTADN resulted in up- or down-regulation of nine stress genes and four virulence-associated genes in E. faecalis and resulted in different stress states. These findings suggested that nisin improved the post-antibacterial effect of MTAD at sub-MIC levels and has considerable potential for use as a modification of MTAD.